2005
DOI: 10.1063/1.2073969
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium/nitrogen and beryllium/nitrogen coimplantation into GaN

Abstract: The nitrogen coimplantation characteristics in the Mg- and Be-implanted GaN with different dopant concentration ratios have been systematically investigated. The Hall-effect measurements show that the p-type characteristics are produced in the Mg- and Be-implanted GaN by the coimplantation of N atoms and subsequent annealing, which is essentially related to the column II/V dopant concentration ratio and annealing condition. This behavior may be attributed to the reduction of self-compensation induced by N vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This makes high pressure annealing too expensive for industry and difficult to scale up to lager wafer sizes. RTA is attractive for GaN annealing in terms of achievable temperatures and costs, but it has not been shown that RTA enables electrical activation of Mg after the implantation in GaN without co-doping with other ions [9]. One probable reason for these unsuccessful attempts of using RTA to activate the implanted Mg is the short duration of the GaN annealing at high temperatures.…”
Section: New Annealing Approachmentioning
confidence: 98%
“…This makes high pressure annealing too expensive for industry and difficult to scale up to lager wafer sizes. RTA is attractive for GaN annealing in terms of achievable temperatures and costs, but it has not been shown that RTA enables electrical activation of Mg after the implantation in GaN without co-doping with other ions [9]. One probable reason for these unsuccessful attempts of using RTA to activate the implanted Mg is the short duration of the GaN annealing at high temperatures.…”
Section: New Annealing Approachmentioning
confidence: 98%
“…It has been reported that the activation of implanted impurities in GaN is difficult compared with that of typical semiconductors . For acceptor‐impurity implantation, nitrogen vacancies ( V N s) are expected to be introduced, and they act as shallow compensating centers.…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy of substitutional Be acceptors is still under debate. Some groups found activation energies between 90 and 150 meV, while others report values between 170 and 250 meV . Lany et al found in their calculations two acceptor states of Be in GaN: a deep localized ground state at around VBM + 0.45 eV, and a shallow effective‐mass‐like delocalized state at around VBM + 0.15 eV .…”
Section: Resultsmentioning
confidence: 99%